Preparation method of gold-silver alloy biocompatible rice particles and urine detection application

Au/Ag-GSH alloy nanoparticles prepared by solvent-free solid-phase grinding method solve the problem of long reaction time and low yield of alloy nanocluster preparation method, and use their fluorescent luminescence characteristics at different pH values ​​to achieve rapid and sensitive detection of urine pH values.

CN116021030BActive Publication Date: 2025-03-14TONGJI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310127361.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-03-14
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

The preparation method of alloy nanoclusters in the prior art has a long reaction time and low yield, and the solvent-free synthesis method has not been successfully applied to the preparation of alloy nanoclusters, and the existing urine pH detection method is not sensitive enough.

Method used

Au/Ag-GSH alloy nanoparticles were prepared by a two-step reduction method of HAuCl4·3H2O, AgNO3 and glutathione by solvent-free solid-phase grinding method, and their fluorescent luminescence characteristics at different pH values ​​were used for urine pH detection.

Benefits of technology

The high yield and environmentally friendly preparation of alloy nanoparticles are achieved, and the prepared nanoclusters have good biocompatibility and luminescence enhancement characteristics under acidic conditions, and can quickly and sensitively detect urine pH.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116021030B_ABST
    Figure CN116021030B_ABST
Patent Text Reader

Abstract

The invention discloses a solvent-free preparation method of gold-silver alloy biocompatible nanoparticles and urine detection use. The preparation method uses HAuCl4·3H2O as an Au source, AgNO3 as an Ag source, NaBH4 as a reducing agent, and glutathione as a ligand to prepare Au / Ag‑GSH alloy nanoparticles by a two-step reduction solid phase grinding method. The preparation process is simple, green and environmentally friendly, short in time, and high in yield. The prepared Au / Ag‑GSH alloy nanoclusters with an average particle size of 2.03±0.12nm are uniform in size, have good biocompatibility and the characteristics of enhanced luminescence under acidic conditions, can be applied to rapid, sensitive, and efficient detection of urine pH, and are easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biofunctional nanomaterials, and more specifically, to a solvent-free preparation method of gold-silver alloy biocompatible nanoparticles and urine detection applications thereof. Background Art

[0002] Alloying of metal nanoclusters is considered an important means to enhance the luminescence of nanoclusters. At present, there are three main methods for synthesizing alloy nanoclusters: hydrothermal co-reduction, two-phase ligand exchange, and in situ two-phase ligand exchange. These synthesis methods have long reaction times and low yields, and some metal salts and their ligands have poor solubility (especially in organic solvents), which seriously affects the yield of synthesized nanomaterials. In recent years, many researchers have been keen on mechanochemical synthesis. The reasons are: (1) green and environmentally friendly. The reaction can be carried out at room temperature, with a small amount of solvent or without solvent, avoiding the pollution to the environment caused by the use of a large amount of solvent; (2) short time consumption and high yield. Mechanochemical synthesis can generally be completed within 10 to 60 minutes, which can greatly shorten the preparation time of materials and ensure high yield. At the same time, solvent-free methods are generally considered to be "more environmentally friendly" because they produce less waste and are more scalable in mass production. However, there is currently no successful application of solvent-free synthesis to the preparation of alloy nanoclusters.

[0003] Urine examination is a commonly used medical examination method, which can reflect a variety of human diseases. The pH value of normal human urine is around 6.5, and its fluctuation range is relatively wide, between 4.5 and 8.0. Acidic urine is more likely to cause stones. In addition, patients with acidosis, gout, high fever and diabetes usually show low urine pH. At present, the main methods for detecting urine pH value are pH test paper, pH meter, etc., but their disadvantage is that they are not sensitive enough. Therefore, the development of fluorescent probes with high sensitivity, good selectivity, short response time, low cost, simple operation and good biocompatibility with pH response for the detection of urine pH is of great significance to the development of modern biology. Summary of the invention

[0004] Due to the above-mentioned defects in the prior art, the present invention provides a solvent-free preparation method of gold-silver alloy biocompatible rice particles and urine detection use thereof.

[0005] To achieve the above object, in a first aspect, the present invention provides a method for preparing gold-silver alloy biocompatible rice particles, characterized in that it comprises the following steps:

[0006] Step S11, a molar part of HAuCl4·3H2O and b molar parts of glutathione are fully mixed by solid phase grinding to form a complex;

[0007] Step S12, c molar parts of AgNO3 are added to the complex ground in step S11 and the grinding is continued to obtain a light yellow mixture;

[0008] Step S13, adding d molar parts of NaBH4 to the light yellow mixture and continuing grinding, the mixture first turns black, and finally a dusty gray mixture is obtained;

[0009] Step S14, after the color of the earth-gray mixture no longer changes, deionized water is added to obtain a reddish brown solution; the reddish brown solution is aged and layered, and the supernatant is taken;

[0010] Step S15, adding ethanol to the supernatant and stirring evenly, standing to separate layers; taking the supernatant and centrifuging to obtain a reddish brown solid; washing the reddish brown solid with ethanol by repeated centrifugation and drying to obtain gold-silver alloy biocompatible rice particles;

[0011] Wherein, taking the total molar fraction of HAuCl4·3H2O, AgNO3 and glutathione as 100 parts, the molar fractions of HAuCl4·3H2O, glutathione and AgNO3 are: a=10-34; b=50-80; c=10-34; and d / b=1-3.

[0012] The preparation method adopts a solvent-free solid phase grinding method, uses HAuCl4·3H2O as an Au source, AgNO3 as an Ag source, NaBH4 as a reducing agent, and glutathione (GSH) as a ligand to prepare Au / Ag-GSH alloy nanoparticles, and the preparation process is environmentally friendly and simple. The ligand GSH has a certain reducing property. When HAuCl4 and GSH are ground together, an Au(I)-GSH complex is first formed, and then AgNO3 is added to grind together to form an Au(I)Ag(I)-GSH complex. Finally, a strong reducing agent NaBH4 is added for co-reduction to form Au / Ag-GSH alloy nanoparticles.

[0013] Further, the molar ratio of HAuCl4·3H2O to AgNO3 is 1.

[0014] Preferably, the volume of ethanol added to the supernatant in step S15 is 1 to 3 times the volume of the supernatant; the centrifugal speed used for centrifugation is 6000 to 12000 r / min; and repeated centrifugal washing with ethanol is washing with ethanol at least 3 times.

[0015] In a second aspect, the present invention provides a gold-silver alloy biocompatible rice particle, characterized in that it is prepared by the above-mentioned preparation method; the gold-silver alloy biocompatible rice particle is a monodisperse nanoparticle with a particle size of 1.5 to 100 nm.

[0016] Preferably, the gold-silver alloy biocompatible nanoparticles are prepared by the above-mentioned preparation method when the molar ratio of HAuCl4·3H2O to AgNO3 is 1; the gold-silver alloy biocompatible nanoparticles are nanoclusters with an average particle size of 2.03±0.12 nm and a spherical microscopic morphology.

[0017] Furthermore, the nanoclusters have good dispersibility in aqueous solution, with a hydrated particle size of 5.52 nm and a dispersion coefficient of 0.19.

[0018] Furthermore, the nanoclusters are dispersed in an aqueous solution with a pH value of 1.0 to 8.0 at a concentration of 0.05 to 2 mg / mL, and the obtained solution is incubated for 0 to 24 hours, and then the fluorescence intensity is tested; the fluorescence intensity and the pH value of the aqueous solution show a multi-segment linear relationship.

[0019] In a third aspect, the present invention provides a use of the gold-silver alloy biocompatible rice particles in detecting the pH value of urine.

[0020] Furthermore, the detection process includes the following steps:

[0021] Step S21, dispersing the gold-silver alloy biocompatible nanoclusters in an aqueous solution at a certain temperature and a pH value of 1.0 to 8.0 at a concentration of 0.05 to 2 mg / mL, incubating the obtained solution for 0 to 24 hours, testing the fluorescence intensity, and obtaining a linear relationship equation between the fluorescence intensity and the pH value of the aqueous solution;

[0022] Step S22, diluting a plurality of urine samples by 10 to 30 times for standby use; adding a certain concentration of gold-silver alloy biocompatible rice clusters to the diluted urine samples, incubating for a certain period of time, and detecting the change in the luminescence intensity of the urine samples before and after the addition of the gold-silver alloy biocompatible rice clusters;

[0023] Step S23, determining the pH value of the urine sample according to the luminescence intensity and the linear relationship equation; and judging whether the sample is at risk of acidosis, gout, high fever, stones and diabetes in combination with other pathological indicators.

[0024] Furthermore, when the pH value of the urine sample is less than 4, the fluorescence intensity of the urine sample is significantly enhanced before and after the addition of the gold-silver alloy biocompatible rice clusters.

[0025] Compared with the prior art, the above invention has the following advantages or beneficial effects:

[0026] (1) The Au / Ag-GSH alloy luminescent nanoparticles are prepared by a two-step reduction solid phase grinding method, which has a simple synthesis process and is green and environmentally friendly; it takes a short time and has a high yield, enriching the synthesis methods of alloy nanoparticles;

[0027] (2) The Au / Ag-GSH alloy nanoclusters prepared in the present invention have uniform size, good biocompatibility and the property of enhanced luminescence under acidic conditions, high sensitivity, low cost and simple operation, and can be used to reflect some diseases related to decreased urine pH. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention and its features and advantages will become more apparent upon reading the detailed description of non-limiting embodiments made with reference to the following accompanying drawings.

[0029] Figure 1 The photoelectron spectrum of Au / Ag-GSH alloy nanoparticles according to one embodiment of the present invention;

[0030] Figure 2 for Figure 1 The enlarged fitting diagram of parts A and B;

[0031] Figure 3 A transmission electron microscope photograph of Au / Ag-GSH alloy nanoparticles according to an embodiment of the present invention;

[0032] Figure 4 The hydrated particle size test result of Au / Ag-GSH alloy nanoclusters according to one embodiment of the present invention;

[0033] Figure 5 The photoluminescence images of Au / Ag-GSH alloy nanoclusters in aqueous solutions with different pH values ​​according to one embodiment of the present invention are shown;

[0034] Figure 6 The photoluminescence intensity of Au / Ag-GSH alloy nanoclusters in aqueous solutions with different pH values ​​according to one embodiment of the present invention;

[0035] Figure 7 This is a linear relationship diagram between the photoluminescence intensity and pH value of Au / Ag-GSH alloy nanoclusters in aqueous solutions with different pH values ​​according to one embodiment of the present invention;

[0036] Figure 8 This is a schematic diagram of the process of detecting urine pH value using Au / Ag-GSH alloy nanoclusters according to one embodiment of the present invention;

[0037] Fig. 9 This is a schematic diagram of pH test paper detecting the pH value of urine sample;

[0038] Fig.10 The photoluminescence images of the Au / Ag-GSH alloy nanoclusters according to one embodiment of the present invention for detecting pH values ​​of three urine samples are shown. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments will be described clearly and completely below. Obviously, the embodiments described below are only part of the embodiments of the present invention, rather than all the embodiments.

[0040] The terms "comprise", "include" and any variations thereof in the following embodiments and comparative examples are intended to cover non-exclusive inclusions, for example, a process, method, or product comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or units that are inherent to these processes, methods, or products.

[0041] In addition, the reaction devices and chemical reagents involved in the following embodiments and comparative examples are all commercially available, and the detection instruments and detection reagents involved are all commercially available.

[0042] The following examples and comparative examples were tested using the following methods, equipment or standards:

[0043] (1) Hydration particle size test: First, prepare the sample to be tested into a 1 mg / mL aqueous solution, then take 30 μL and dilute it to 3 mL and place it in a dynamic light scattering instrument to measure its hydrated particle size in the aqueous solution;

[0044] (2) Fluorescence spectrum test: The gold-silver alloy biocompatible nanoclusters were dispersed in an aqueous solution with a pH value of 1.0 to 8.0 at a concentration of 1 mg / mL, and the resulting solution was incubated for 0 to 24 hours. 300 μL was placed in a 1 mm cuvette and measured on a fluorescence spectrometer.

[0045] Example 1

[0046] This embodiment provides a method for preparing gold-silver alloy biocompatible rice particles. First, prepare a grinding tool: soak the grinding tool in a newly prepared aqua regia for a period of time, then clean it with distilled water, put it in an oven to dry, then take it out and cool it for later use. The grinding tool can be a mortar or a mechanical grinding tool such as a ball mill. The method for preparing gold-silver alloy biocompatible rice particles includes the following steps:

[0047] Step S11, a molar part of HAuCl4·3H2O and b molar parts of glutathione are fully mixed by solid phase grinding to form a complex;

[0048] Step S12, c molar parts of AgNO3 are added to the complex ground in step S11 and the grinding is continued to obtain a light yellow mixture;

[0049] Step S13, adding d molar parts of NaBH4 to the light yellow mixture and continuing grinding, the mixture first turns black, and finally a dusty gray mixture is obtained;

[0050] Step S14, after the color of the earth-gray mixture no longer changes, deionized water is added to obtain a reddish brown solution; the reddish brown solution is aged and layered, and the supernatant is taken;

[0051] Step S15, adding ethanol to the supernatant and stirring evenly, standing to separate layers; taking the supernatant and centrifuging to obtain a reddish brown solid; washing the reddish brown solid with ethanol by repeated centrifugation and drying to obtain gold-silver alloy biocompatible rice particles;

[0052] Wherein, taking the total molar fraction of HAuCl4·3H2O, AgNO3 and glutathione as 100 parts, the molar fractions of HAuCl4·3H2O, glutathione and AgNO3 are: a=10-34; b=50-80; c=10-34; and d / b=1-3.

[0053] The preparation method uses HAuCl4·3H2O as an Au source, AgNO3 as an Ag source, NaBH4 as a reducing agent, and glutathione (GSH) as a ligand. The ligand GSH has a certain reducing property. When HAuCl4 and GSH are ground together, an Au(I)-GSH complex is first formed, and then AgNO3 is added to grind together to form an Au(I)Ag(I)-GSH complex. Finally, a strong reducing agent NaBH4 is added for co-reduction to form Au / Ag-GSH alloy nanoparticles.

[0054] As a preferred technical solution, further:

[0055] The volume of ethanol added to the supernatant in step S15 is 1 to 3 times the volume of the supernatant; the centrifugal speed used for centrifugation is 6000 to 12000 r / min; and repeated centrifugal washing with ethanol is washing with ethanol at least 3 times.

[0056] To further help understand the technical solution of this embodiment, the technical solution of this embodiment is described in more detail below through several specific examples.

[0057] Example 1:

[0058] (1) Weigh a certain amount of HAuCl4·3H2O and GSH and add them to a cleaned mortar and grind for 10 min to ensure that GSH and HAuCl4·3H2O are fully mixed to form a complex. The molar ratio of HAuCl4·3H2O to GSH is 1:3.

[0059] (2) Weigh a certain amount of AgNO3 and add it to the above-ground mixture and continue grinding for 10 minutes. After the three are completely mixed, weigh a certain amount of NaBH4 and add it to the mixture and continue grinding for 10 minutes. During this process, the color of the mixture changes from the previous light yellow to black when it is just added, and it becomes a dusty gray solid after 10 minutes. The molar ratio of the amount of AgNO3 added to the amount of GSH added in step (2) is 1:3, and the molar ratio of HAuCl4·3H2O and AgNO3 is 1:1. The molar ratio of the added NaBH4 to GSH is 1:1.

[0060] (3) After the color stops changing, slowly add deionized water (1 mL at a time, grinding while adding), the volume of deionized water added is 10-20 mL, and grind for 5-10 minutes to obtain a reddish-brown solution. The obtained solution is aged for a period of time, and the larger nanoparticles are precipitated at the bottom. At this time, use a pipette to slowly transfer the supernatant to a clean container, and then add ethanol, stir evenly with a glass rod, and let the solution stand to separate. Nanoclusters and large nanoparticles will dissolve in the aqueous solution. Dispersing with ethanol can make nanoclusters with smaller particle sizes dispersed in the ethanol solution, while nanoparticles with larger particles dissolve in water. Using ethanol to separate the aqueous solution can obtain more uniform nanoclusters.

[0061] (4) The supernatant of the layered ethanol solution is centrifuged, and then the obtained solid is repeatedly washed with ethanol. Finally, the obtained reddish brown solid is placed in a vacuum drying oven for drying, and Au / Ag-GSH alloy nanoparticles are obtained. The volume of the appropriate amount of ethanol added is 1 to 3 times the volume of the supernatant. The centrifugal speed of the centrifuge used for centrifugation is one of 6000r / min, 8000r / min, 10000r / min, and 12000r / min. Repeated washing with ethanol means washing with ethanol at least 3 times.

[0062] Examples 2 to 13 use a similar method to Example 1 to prepare Au / Ag-GSH alloy nanoparticles, except that the feed ratios of the raw materials used are different. The specific feed ratios are shown in Table 1.

[0063] Table 1 Feed ratio of HAuCl4·3H2O, AgNO3 and GSH in each example

[0064]

[0065]

[0066] The composition and morphology of the Au / Ag-GSH alloy nanoparticles obtained in Examples 1 to 13 were observed. Figure 1 and Figure 2The photoelectron spectrum (XPS) of the Au / Ag-GSH alloy nanoparticles obtained in Example 4. The XPS test results show that Au(I) and Ag(I) coexist in the Au / Ag-GSH peripheral motif, indicating that the product is an Au / Ag alloy with GSH ligands. It can be seen from the transmission electron microscopy photos of Examples 1 to 13 that the prepared gold-silver alloy biocompatible nanoparticles are monodisperse nanoparticles with a particle size of 1.5 to 100 nm. When the molar fraction of AgNO3 is greater than the molar fraction of HAuCl4·3H2O, nanoparticles with a particle size of about 50 nm are formed. When the molar fraction of HAuCl4·3H2O is greater than the molar fraction of AgNO3, a larger aggregate is formed. Only when the molar ratio of HAuCl4·3H2O to AgNO3 is 1:1, especially when the molar ratio of HAuCl4·3H2O:AgNO3:GSH is 1:1:6, nanoclusters with a particle size less than 2nm are formed. Figure 3 Only the transmission electron micrographs of the Au / Ag-GSH alloy nanoparticles obtained in Examples 4, 7 and 10 are shown. It can be seen that only the Au / Ag-GSH alloy nanocluster of Example 4 has a spherical microscopic morphology, the nanocluster size is uniform, and the average particle size is 2.03±0.12nm. The nanoparticles of Examples 7 and 10 are nanoparticles with a particle size greater than 50nm.

[0067] The Au / Ag-GSH alloy nanoclusters prepared in Example 4 were subjected to dynamic light scattering detection. Figure 4 It can be seen that the average particle size of the synthesized Au / Ag-GSH alloy nanoclusters is about 5.52nm, which is consistent with the TEM statistical results. In addition, it is proved that the nanoclusters have good dispersibility in aqueous solution, and their dispersion coefficient PDI is 0.19.

[0068] Example 2

[0069] This embodiment provides a gold-silver alloy biocompatible nanocluster with luminescence enhancement properties.

[0070] Taking Example 4 of Example 1 as an example, the gold-silver alloy biocompatible nanoparticles are nanoclusters with an average particle size of 2.03±0.12 nm. The nanoclusters are dispersed in an aqueous solution with a pH value of 1.0 to 8.0 at a concentration of 0.05 to 2 mg / mL, and the obtained solution is incubated for 0 to 24 hours, and the fluorescence intensity is tested; the fluorescence intensity and the pH value of the aqueous solution have a multi-segment linear relationship.

[0071] To further help understand the technical solution of this embodiment, the technical solution of this embodiment is described in more detail below through several specific examples.

[0072] The specific operation of Examples 14 to 25 is: add Au / Ag-GSH alloy nanoclusters to an aqueous solution with a pH value of 1.0 to 8.0 at 37°C, incubate for 0 to 24 hours, and track the change of its luminescence intensity using fluorescence spectroscopy. The relevant linear relationship equation is obtained according to the luminescence intensity corresponding to different pH values. The different solution pH values ​​in each example are shown in Table 2.

[0073] Table 2 Solution pH values ​​corresponding to each example

[0074]

[0075]

[0076] See also Figure 5 and Figure 6 The pH value of the solution has a great influence on the luminescence of Au / Ag-GSH alloy nanoclusters, especially in an acidic environment. In a solution with a pH greater than 4, the Au / Ag-GSH alloy nanoclusters can exist relatively stably without assembly or aggregation, so the luminescence performance does not change much. When the pH value of the solution shown is less than or equal to 3, the Au / Ag-GSH alloy nanoclusters gradually change to a neutral form, and then the GSH ligands aggregate through hydrogen bonds between carboxyl and amino groups, restricting intramolecular rotation (RIR) to form a larger rigid structure, which ultimately leads to fluorescence enhancement. See Figure 7 There are two linear relationships between the fluorescence intensity of Au / Ag-GSH alloy nanoclusters and the pH value of the aqueous solution. In the pH range of 1 to 3, the fluorescence intensity is positively correlated with the pH value of the aqueous solution, and in the pH range of 3 to 6, the fluorescence intensity is negatively correlated with the pH value of the aqueous solution.

[0077] Example 3

[0078] This embodiment provides a use of a gold-silver alloy biocompatible rice cluster in detecting the pH value of urine.

[0079] As an example, see Figure 8 The process of using the gold-silver alloy biocompatible rice clusters obtained in Example 4 to detect the pH value of urine includes the following steps:

[0080] Step S21, dispersing the gold-silver alloy biocompatible nanoclusters in an aqueous solution at a certain temperature and a pH value of 1.0 to 8.0 at a concentration of 0.05 to 2 mg / mL, incubating the obtained solution for 0 to 24 hours, testing the fluorescence intensity, and obtaining a linear relationship equation between the fluorescence intensity and the pH value of the aqueous solution;

[0081] Step S22, diluting a plurality of urine samples by 10 to 30 times for standby use; adding a certain concentration of gold-silver alloy biocompatible rice clusters to the diluted urine samples, incubating for a certain period of time, and detecting the change in the luminescence intensity of the urine samples before and after the addition of the gold-silver alloy biocompatible rice clusters;

[0082] Step S23, determining the pH value of the urine sample according to the luminescence intensity and the linear relationship equation; and judging whether the sample is at risk of acidosis, gout, high fever, stones and diabetes in combination with other pathological indicators.

[0083] See also Figure 8 When the pH value of the urine sample is less than 4, the fluorescence intensity of the urine sample is significantly enhanced before and after the addition of the gold-silver alloy biocompatible rice clusters. Fig. 9 , the pH values ​​of three urine samples were tested using common pH test paper.

[0084] See also Fig.10 As shown in Table 3, in the urine samples of three groups of people (Urine 1, Urine 2, Urine 3), Au / Ag-GSH alloy nanoclusters have good biocompatibility and show good properties of luminescence enhancement under acidic conditions. According to the different luminescence intensities in different urine samples, we can accurately know the pH value of urine, and then judge whether it is acidic urine, and then judge whether it is at risk of acidosis, gout, high fever, stones and diabetes in combination with other pathological indicators. Compared with the traditional pH test paper method, the method of the present invention is faster, more sensitive, more efficient, and easier to operate.

[0085] Table 3 Results of detecting actual urine pH using pH test paper and Au / Ag-GSH alloy nanoclusters

[0086] Urine 1(pH) Urine 2(pH) Urine 3(pH) pH Test Paper 1-3 4-6 5-7 Au / Ag-GSH 2.34 4.56 6.15

[0087] In summary, the present invention discloses a solvent-free preparation method of a gold-silver alloy biocompatible nanoparticle cluster and its urine detection application. The preparation method uses HAuCl4·3H2O as an Au source, AgNO3 as an Ag source, NaBH4 as a reducing agent, and glutathione as a ligand to prepare Au / Ag-GSH alloy nanoparticles by a two-step reduction solid phase grinding method. The preparation process is simple, green and environmentally friendly, time-saving, and high in yield. The prepared Au / Ag-GSH alloy nanoclusters with an average particle size of 2.03±0.12nm are uniform in size, have good biocompatibility and the characteristics of enhanced luminescence under acidic conditions, can be applied to the rapid, sensitive, and efficient detection of urine pH, and are easy to operate.

[0088] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.

[0089] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.

Claims

1. A use of gold-silver alloy biocompatible rice particles in detecting urine pH value, characterized in that: The method for preparing the gold-silver alloy biocompatible rice particles comprises the following steps: Step S11, a molar part of HAuCl4·3H2O and b molar parts of glutathione are fully mixed by solid phase grinding to form a complex; Step S12, c molar parts of AgNO3 are added to the complex ground in step S11 and the grinding is continued to obtain a light yellow mixture; Step S13, adding d molar parts of NaBH4 to the light yellow mixture and continuing grinding, the mixture first turns black, and finally a dusty gray mixture is obtained; Step S14, after the color of the earth-gray mixture no longer changes, deionized water is added to obtain a reddish brown solution; the reddish brown solution is aged and layered, and the supernatant is taken; Step S15, adding ethanol to the supernatant and stirring evenly, standing to separate layers; taking the supernatant and centrifuging to obtain a reddish brown solid; washing the reddish brown solid with ethanol by repeated centrifugation and drying to obtain gold-silver alloy biocompatible rice particles; Wherein, based on the total molar fraction of HAuCl4·3H2O, AgNO3 and glutathione as 100 parts, the molar fractions of HAuCl4·3H2O, glutathione and AgNO3 are: a = 10-34; b = 50-80; c = 10-34; and d / b = 1-3; a / c = 1; The prepared gold-silver alloy biocompatible rice particles are monodisperse gold-silver alloy biocompatible rice clusters with an average particle size of 2.03±0.12 nm; The urine pH test process includes the following steps: Step S21, dispersing the gold-silver alloy biocompatible rice clusters in an aqueous solution with a pH value of 1.0 to 8.0 at a certain temperature at a concentration of 0.05 to 2 mg / mL, incubating the obtained solution for 0 to 24 hours, testing the fluorescence intensity, and obtaining a multi-segment linear relationship equation between the fluorescence intensity and the pH value of the aqueous solution; Step S22, diluting a plurality of urine samples by 10 to 30 times for standby use; adding a certain concentration of gold-silver alloy biocompatible rice clusters to the diluted urine samples, incubating for a certain period of time, and detecting the change in the fluorescence intensity of the urine samples before and after the addition of the gold-silver alloy biocompatible rice clusters; Step S23, determining the pH value of the urine sample according to the fluorescence intensity and the linear relationship equation; When the pH value of the urine sample is less than 4, the fluorescence intensity of the urine sample is significantly enhanced before and after the addition of the gold-silver alloy biocompatible rice clusters.

2. The use of the gold-silver alloy biocompatible rice particles in detecting the pH value of urine according to claim 1, characterized in that: The volume of ethanol added to the supernatant in step S15 is 1 to 3 times the volume of the supernatant; the centrifugal speed used for centrifugation is 6000 to 12000 r / min; and repeated centrifugal washing with ethanol is washing with ethanol at least 3 times.

3. Use of the gold-silver alloy biocompatible rice particles according to claim 1 or 2 in detecting the pH value of urine, characterized in that: The microscopic morphology of the gold-silver alloy biocompatible nanoclusters is spherical.

4. The use of the gold-silver alloy biocompatible rice particles in detecting the pH value of urine according to claim 3, characterized in that: The gold-silver alloy biocompatible rice clusters have good dispersibility in aqueous solution, with a hydrated particle size of 5.52 nm and a dispersion coefficient of 0.19.

Citation Information

Patent Citations

  • Precious metal nanoparticle composite SERS fiber and preparation method and application thereof

    CN111793855A

  • Controllable preparation of near-infrared luminous glutathione protected gold nano-cluster and luminous property regulation and control method of near-infrared luminous glutathione protected gold nano-cluster

    CN114686214A

  • Method for preparing gold nanoclusters by using solid-phase dynamic control method

    CN115283688A